The Relationship between Progressivism Educational Philosophy and Science and Its Relevance in the Era of the Industrial Revolution 4.0 (Society 5.0) - Syahidi, Khaerus; Sarjan, Muhammad; Rokhmat, Joni; A, Syahrial; Mertha, I Gde; Arizona, Kurniawan; Syamsuddin, Syamsuddin; Sucilestari, Ramdhani (Kappa Journal, 2023)
Philosophy and science are human efforts to understand the concepts and methods of a scientific discipline. Changing times and developments have ushered in a philosophy of configuration by showing how the "tree of knowledge" thrives and branches out from the respective disciplines. This study aims to examine philosophy and science and their relevance in the Industrial Revolution 4.0 era. This research method uses the hermeneutic method in explaining the reality that occurs with elements of interpretation and description. The results of the research can be described that the study of the relationship between philosophy and science has developed so rapidly. Philosophy and science are indispensable in the development of science and technology which is marked by sharpening of scientific specialization, because by studying philosophy scientists are expected to be aware of its limitations so as not to get caught up in intellectual arrogance. It is impossible to fight against the discourse on the development of science and technology, but rather to reduce the negative impact of technology itself. In the era of the Industrial Revolution 4.0 and Society 5.0, community groups are heterogeneous, so that very complex problems arise related to technological developments and can change the mindset of human life to patterns of life that are more sophisticated with the power of technology. like robots and the internet. Thus, science which is used as an axiological milestone in directing and controlling the development of science and technology in a positive way for the benefit of humanity and its environment is philosophy and science.